Doğu Akdeniz'de Petrol Kirliliğinin Modellenmesi - Onay, Muhittin Güneş (Fen Bilimleri Enstitüsü, 2016)
Globalleşmenin etkisi, enerji gereksiniminin artması ve ticaret hacminin büyümesi ile daha az maliyetli olan deniz yolu taşımacılığına olan talep artmıştır. Bu taşıma süresince gittikçe artan bir şekilde deniz kazaları oluşmakta ve deniz ortamı bu kazalar sonucunda denize dökülen petrol ürünlerinden ciddi boyutlarda kirlenmektedir. Bu kirlilik, ekonomik ve çevresel faktörler ile meydana geldiği bölgeyi olumsuz yönde etkilemektedir. Bu çalışmada üç boyutlu hidrodinamik ve taşınım modeli olan MOHID kullanılarak petrol kirliliğinin yayılımı incelenmiştir. Çalışma bölgesi olarak Türkiye için stratejik önemi haiz petrol rafinerilerinin ve dolum istasyonlarının yoğun olduğu Doğu Akdeniz bölgesi seçilmiştir. Doğu Akdeniz jeopolitik konumu ile Türkiye’nin önemli deniz ticaret yollarını ve limanlarını içine almaktadır. Doğu Akdeniz’de gemi trafik akışının yoğun olduğu, Mersin önleri ve İskenderun Körfezi için kaza senaryoları üretilmiştir. Bölgedeki olası gemi kazası sonrası yakıt kirliliği simülasyonu yapılarak, bölgedeki yakıt dağılımı sonlu hacimler yöntemi ile hesaplanmıştır. Model, her bir zaman adımında petrolün alansal dağılımını vermektedir. Model, petrol dağılımını atmosferik koşullara, tanımlanmış başlangıç ve sınır koşullarına göre hesaplamaktadır. Model validasyonu, Coriolis projesi kapsamında Mart 2014’de Mersin önlerinde denize bırakılan şamandıranın topladığı verilerin, model verileri ile karşılaştırılması ile yapılmıştır. Model bu tarihlerde çalıştırılmış olup, şamandıra verilerine benzer sonuçlar vermiştir. Simülasyona başlamadan önce modelin stabil olmasını sağlamak için model ısınma periyodunda çalıştırılmıştır. Isınma periyodu iki aşamada gerçekleşmiştir. İlk olarak birincil çalıştırma, müteakiben ikincil çalıştırma yapılmıştır. Birincil çalıştırmada veriler anlık olarak değil belli bir zamana yayılarak uygulanmıştır. Bu şekilde modelin hata vermesi engellenmiştir. İkincil çalıştırma, hesaplamalarına birincil çalıştırmadan elde edilen verileri başlangıç noktası alarak devam etmiştir. Model yaz ve kış mevsiminde meydana gelecek kirlilik senaryoları için dört gün boyunca çalıştırılmıştır. Yaz mevsimi simülasyon sonuçları incelendiğinde, kirliliğin İskenderun Körfezi’nde, İskenderun ve Dörtyol ilçesi kıyılarını etkileyeceği, Mersin bölgesinde ise Kazanlı kıyılarını etkileyeceği beklenmektedir. Kış mevsimi simülasyon sonuçları incelendiğinde ise, İskenderun Körfezi’nde uzunca bir sahil şeridinin kirliliğe maruz kalacağı, Mersin bölgesinde de kirliliğin kıyıya paralel olarak hareket edeceği beklenmektedir.

Energy demand of the world has increased significantly with the industrial development. However, the development of industries and technology has led to an increase of environmental risks all over the world. With the increasing demand for oil, oil exploration and trasnportation have also increased to meet the demand, leading to an increase in the risk of oil spill accidents Although seaway transportation is cheaper than other types of transportation, it is the riskiest way considering the possible accidents and their widespread effects. Many factors may lead to accidents in the sea and cause irrecoverable man-made disasters. Due to inadequate training of officers and crew, faulty construction of ships, lack of proper equipment, overloading and lack of attention, inevitable ship accidents may occur. Ship accidents negatively affect the region where it takes place by the means of economics and environmental aspects. In the present, main source for energy is oil and transportation of oil is generally done via sea transportation due to relatively low costs. Although increased tanker traffic is the biggest risk for the oil pollution in the seas, it is not the only one. Dry cargo or container carrying ships also can cause oil spill to the sea in the case of any breakdown or accident in their fuel tanks. In addition to these, illegal discharges to the sea such as bilge or ballast water discharges may cause oil spill to the sea. Oil pollution is one of the most serious environmental problems worldwide, since oil spills are causing significant, long-term impacts on the affected area environmentally, ecologically, and socio-economically. Fresh water and marine environments are seriously affected by oil spill. Besides the point that it affects the natural resources negatively, it also affects a wide range of organisms through the complex food chain and these impacts can even reach to human food resources. Damages after an oil spill can be in different ways in the environment. It can directly affect the environment and wildlife physically, or oil can cause toxicity to the exposed organisms. These impacts depend on several factors, including the physical and chemical properties of the spilled oil, and the fate of it. In this study, three dimensional hydrodynamic and transportation model MOHID was used to simulate oil spill. MOHID software lets the user to build a tree of one-way nested models without limitations on the numerous of nesting levels. In this work, modeling studies performed using two models: one for the whole system (main model), and the other one for the study area (submodel) with a more detailed grid. One-way downscaling scheme (nested models) was used to join these two models. To define the hydrodynamic and water properties, the main model which consisted of a less detailed grid was used and boundary conditions are supplied for the submodel. The connection between the main model and the submodel was provided by the assimilation of the relaxed solutions in a band of cells of the main model by the submodel. The information transfer was maintained as one-way direction, from the main model to the submodel. So, the submodel was enforced to use the boundary conditions acquired from the main model. At the first run of each new simulation, cold start was done for stability purposes. The wind is the main factor affecting hydrodynamic fields. The hydrodynamic fields are used to force a Lagrangean oil spill model to simulate a hypothetical oil spill in potentially risky areas. A finite volume methodology with a generic vertical coordinate system is used in this model. The wind data was slowly imposed to the model over a period of time. This way, the model does not accept any previous results as a starting point. The second run was done after this cold start as a continuous run of the first. This hot start accepted the data from the cold start as the starting point. East Mediterranean contains important sea trade ways and ports because of its important geopolitic location. Therefore, Mersin and İskenderun areas in Turkey was selected as the study area, due to the fact that the area is strategically very important with the refineries and filling stations. Ship accident scenarios were created for the locations where vessel traffic is heavy. Oil spill pollution after possible tanker accidents in the region, were simulated and oil spill was calculated by using finite volumes. Three dimensional developed model provides area distribution in every time step. The model calculates the spread of the oil spill based on the current conditions and predetermined boundary conditions. In the model, constantly changing wind speed and direction were used which were taken from SKIRON forecast system which is a full physics atmospheric model with several unique capabilities that make it appropriate for regional/mesoscale simulations in regions with highly variable physiographic characteristics. Sea water temperature, salinity, water level and current data are initial and boundary conditions. They were obtained from MERCATOR Ocean which is the French Center for analysis and forecasting of the global ocean, as service provider of ocean information in real and delayed time. In the model, different scenarios were created for different coordinates with high accident risks as well as for summer and winter conditions. In March 2014, a drifter was released the cost of Mersin in scope of Coriolis Project and the data were published as an open source. For validating the model results, the time period was selected as March 2014 and model data were compared with real data obtained from the drifter. Also, meteorological and atmospherical data for March 2014 were used. Unlike previous studies, constantly changing wind speed and wind direction data were used instead of constant wind data to get more reliable results from the modeling study. In East Mediterranean, the prevailing wind blows from south west for summer and north and north east for winter. The model was run for the summer and winter separately; the prevailing wind was configured as south west for the summer and north and north east for the winter to obtain a realistic view of pollution in case of any real accident. According to model outputs, in case of an accident off the cost of BOTAŞ in summer conditions, Dörtyol district will be exposed to oil pollution. The pollution reaches to the shore after 43 hours. In winter conditions, a possible pollution in the area would proceed parallel to shore area, and if no precaution is taken, the pollution will reach to the off the cost of baymouth. According to the model outputs, in summer conditions, in case of an accident off the cost of İskenderun, North İskenderun area as well as the iron and steel factory shore area will be exposed to oil pollution. The pollution will reach to the shore after 24 hours. At the end of four days, the pollution would expand towards the coast line, and reach off the cost of Dörtyol district. In winter conditions, a possible pollution will reach to the shore after 24 hours similar to summer conditions. If no precaution is taken, the pollution would affect a long coast line through İskenderun. According to the model outputs, in summer conditions, in case of an accident off the coast of Mersin, Kazanlı coastal area will be exposed to oil pollution. The pollution reaches to the shore after 36 hours. At the end of four days, all the oil would be accumulated in the coastline. In winter conditions, a possible pollution in the area, will distribute parallel to the coast line and at the end of four days, the pollution will reach Erdemli district. In summer and winter conditions, applying a barrier set before oil pollution during emergency situations may prevent the spread of pollution over larger areas.
Oil Spill Modeling In East Mediterranean
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Petrol Kirliliği; Yayılım; Sayısal Modelleme; Mohıd; Doğu Akdeniz; Deniz Çevresi; Hidrodinamik Alanlar; Gemi Kazası; Oil Spill; Spreading; Numerical Modeling; Mohid; East Mediterranean; Marine Environment; Hydrodynamic Fields; Ship Accident